Pengaruh Pijat Efleurage Terhadap Penurunan Nyeri Dismenore Pada Remaja Putri - Ika Nur Saputri; Riza Ardila Verawati Lubis; Irma Nurianti; Novita Br Ginting Munthe (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
Every woman will always experience menstruation every month, this can cause dysmenorrhea caused by prostaglandin production such as menstrual pain in the form of cramps in the lower abdomen in the pelvic area which results in disruption of activities and quality of life. This study aims to determine the effect of effleurage massage on reducing menstrual pain in young women. This type of research uses a quasi-experimental design with one group pretest and posttest while the sampling technique is purposive sampling. The results showed that the p-value before and after effleurage massage therapy was 0.000 (<0.05). The results of the study concluded that Ha was accepted and Ho was rejected because there was a significant effect before and after being given effleurage massage on reducing dysmenorrhea pain in young women.